Leveraging model-based study designs and serial micro-sampling techniques to understand the oral pharmacokinetics of the potent LTB4 inhibitor, CP-105696, for mouse pharmacology studies. (3rd July 2017) - Spilker, Mary E.; Chung, Heekyung; Visswanathan, Ravi; Bagrodia, Shubha; Gernhardt, Steven; Fantin, Valeria R.; Ellies, Lesley G.
Abstract: 1. Leukotriene B4 (LTB4) is a proinflammatory mediator important in the progression of a number of inflammatory diseases. Preclinical models can explore the role of LTB4 in pathophysiology using tool compounds, such as CP-105696, that modulate its activity. To support preclinical pharmacology studies, micro-sampling techniques and mathematical modeling were used to determine the pharmacokinetics of CP-105696 in mice within the context of systemic inflammation induced by a high-fat diet (HFD). 2. Following oral administration of doses > 35 mg/kg, CP-105696 kinetics can be described by a one-compartment model with first order absorption. The compound's half-life is 44–62 h with an apparent volume of distribution of 0.51–0.72 L/kg. Exposures in animals fed an HFD are within 2-fold of those fed a normal chow diet. Daily dosing at 100 mg/kg was not tolerated and resulted in a >20% weight loss in the mice. 3. CP-105696's long half-life has the potential to support a twice weekly dosing schedule. Given that most chronic inflammatory diseases will require long-term therapies, these results are useful in determining the optimal dosing schedules for preclinical studies using CP-105696.